Fatal dissection of the pulmonary artery in pulmonary arterial hypertension - B. Degano; G. Prevot; L. Têtu; O. Sitbon; G. Simonneau; M. Humbert (European Respiratory Review, 2009)
A 41-yr-old patient with chronic stable idiopathic pulmonary arterial hypertension (PAH) presented with sudden chest pain and unusual dyspnoea during physical exertion. The patient had been diagnosed with PAH at the age of 12 yrs and was in New York Heart Association functional class I/II. The patient was being treated with an anticoagulant regimen, low-dose diuretics and continuous intravenous epoprostenol therapy. A computed tomography scan showed ancient massive thrombi in dilated central pulmonary arteries, which were not haemodynamically significant (perfusion lung scans did not demonstrate segmental or larger defects), and extensive dissection of the right pulmonary artery starting from the intermediate branch. Due to the extensiveness of the dissection, the patient was immediately considered for heart–lung transplantation, but died 72 h after the onset of symptoms. Permission for post mortem examination was denied. Pulmonary artery dissection should be suspected in PAH patients presenting with chest pain and worsening dyspnoea. In the current case, the factors possibly associated with increased risk for dissection may include dilatation of the pulmonary artery, local inflammation favoured by in situ thrombosis, and acute increase of pulmonary pressure secondary to physical exertion. Extensive pulmonary artery dissection is a life-threatening complication of PAH, and urgent heart/lung transplantation might be the treatment of choice in eligible patients. In addition, better identification of the risk factors for pulmonary artery dissection may help in considering transplantation for selected patients at risk.